Karakteristik Tegangan dan Regangan Tarik Pada Komposit CFRP Yang Berlubang - Ikhsan, Muhammad; Sudarsono, Sudarsono; Endriatno, Nanang (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2021)
In the industrial world, the development of material technology is growing rapidly. There is an increasing demand for materials with certain properties such as perforated composites. The consideration of perforated composites is an important parameter in the design of composite components. The purpose of this study was to determine the tensile stress and strain characteristics of hollow CFRP composites. The research method used is to analyze the tensile test using abaqus software, the tensile test analysis is carried out with 3 variations in the diameter of the hole (2 mm, 4 mm, and 6 mm). From the tensile test simulation results, it is found that the highest stress occurs in the 6 mm diameter composite with a maximum stress value of 180.4 N/mm², and the lowest stress occurs in the 2 mm diameter composite with a maximum stress value of 102.6 N/mm². The highest stress and strain that occurs in each specimen is located on the edge of the hole perpendicular to the direction of the force, the stress and strain increase based on the diameter of the hole in the composite, the larger the diameter in the composite, the greater the stress that occurs..Keywords: Tensile test, CFRP composite, abaqus software